Sustainability assessment of healthcare waste treatment systems using surrogate weights and PROMETHEE method - Makan, Abdelhadi (Waste management & research : the journal of the International Solid Wastes and Public Cleansing Association, ISWA, 2021)
This study aims to assess the sustainability of healthcare waste treatment systems using surrogate weights and the Preference Ranking Organization METHod for Enrichment Evaluations (PROMETHEE). For this purpose, ten treatment systems, including land disposal, incineration and non-incineration systems, were evaluated in terms of environmental, financial, social, and technical criteria. Firstly, fifteen reputed experts assigned their preferred rankings for the groups of criteria and the sub-criteria. The conversion of these rankings into numerical weights was performed using the SR function, which is an additive combination of Sum and Reciprocal weight functions. Secondly, the alternatives' performance with regards to each criterion allowed PROMETHEE to generate the outranking flows for each alternative. The complete ranking revealed that the rotary kiln (A4) is the most sustainable system followed by steam disinfection (A8), dry heat disinfection and microwave disinfection. However, the municipal landfill is the least sustainable system, while chemical disinfection is ranked in the penultimate position of sustainability. The partial ranking indicated that A4 and A8 are incomparable and both were ranked as most sustainable. Therefore, the sustainability of a system cannot be assessed properly without the exact specification of the system itself. In addition, it is preferable to act on the criteria that affect negatively the system to improve its performance